Tributes to Bob Jahn - Dunne, Brenda (Journal of Scientific Exploration, 2018)
I sincerely appreciate the kind tributes to Bob Jahn in the Spring and Fall issues of JSE by Henry Bauer, York Dobyns, Roger Nelson, Tony Edwards, William Bengston, and Peter Sturrock. As you all know, SSE was very close to Bob's heart, for it's community as well as it's mission. He always looked forward to the annual (and European) meetings and the opportunities they presented for reconnecting with old friends, and making new ones,as well as for the intellectual stimulation they provided. And he took great satisfaction in being able to serve on the Council and support the organization in any way he could. I know he would be deeply touched by all your warm remembrances, as am I.